NEW PAPER FORMAT & SUBMISSION GUIDELINES ---------------------------------------------------------------->>>>>MS-Word - *, * (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2020)
Download the Guidelines and submit your paper only as a Microsoft Word document. Any paper not submitted in the NEW required format will be discarded.